Reflection seismic study of the Siljan Ring impact structure: Mora - Raw data - Juhlin, Christopher; Sturkell, Erik; Ebbestad, Jan Ove R.; Lehnert, Oliver; Högström, Anette E. S.; Meinhold, Guido (Uppsala University, 2018)
Two new reflection seismic profiles over the Paleozoic successions of the western part of the Siljan Ring impact structure were acquired during 2011, the Mora and the Orsa profile. This data set concerns the Mora profile. The profile has length of c. 10 km and the processed data image the geological section to about 3 km depth. During the survey, 391 source points (VIBSIST 3000) were recorded by 320 receiver channels for 30 seconds. From this recording, the following data sets were generated and are published here: 1) decoded and quality controlled raw data; 2) pre-processed (shot geometry applied) data; 3) stacked data; 4) migrated data; 5) depth converted data and velocity field.
Key acquisition parameters are:
Number of channels: 320 (160-160)
Near offset: 0m
Geophone spacing: 10 m
Geophone type: 28 Hz single
Source spacing: 20 m
Source type: VIBSIST 3000
Hit interval between hammer blows: 100-200 ms
Sweeps per source point: 3-4
Nominal fold: 80
Recording instrument: SERCEL 428UL
Sample rate: 1 ms
Field low cut: Out
Field high cut: 400 Hz
Record length: 30 s
Profile length: 10 km
Source points: 391
Dates acquired: 3/6-9/6: 2011

This dataset contains the raw data of the Mora profile after decoding the sweep signal the VIBSIST 3000 source.
Processing steps for this data set:
1: Read decoded VIBSIST data
File format: SEGD rev 2; Field acquisition notes scanned to PDF

Access data by contacting request@snd.gu.se or by using the web form.

År 2011 gjordes två nya reflexionsseismiska undersökningar över västra delen av Siljansringen, Mora och Orsa profilerna. Siljansringen är en struktur som uppkom för ca 377 miljoner sedan genom ett meteoritnedslag. Mora profilen (detta dataset) är ca 10 km lång och visar de geologiska strukturerna till ca 3 km djup. Den seismiska bilden visar att den geologiska följden i de siluriska och ordoviciska sedimentera bergarterna är starkt störd.

En mer detaljerad beskrivning av datasetet som inkluderar alla viktiga parametrar är tillgängligt på den engelska katalogsidan: https://snd.gu.se/en/catalogue/study/SND1050

Datasetet innehåller rådata för Mora-profilen, efter avkodning.
Mer information på den engelska katalogsidan: https://snd.gu.se/en/catalogue/study/SND1050.

För tillgång till data kontakta request@snd.gu.se eller använd beställningsformuläret i katalogen.
Reflection seismic study of the Siljan Ring impact structure: Mora - Raw data
Keywords: EARTH SCIENCE; geological disaster; geologisk katastrof; geophysics; geofysik; research; forskning; Geophysics; Geofysik; Geoscientific Information; Geovetenskap